2002
DOI: 10.1021/la010214+
|View full text |Cite
|
Sign up to set email alerts
|

Wormlike Micelles as “Equilibrium Polyelectrolytes”:  Light and Neutron Scattering Experiments

Abstract: We demonstrate that aqueous solutions of giant polymer-like nonionic micelles “doped” with small amounts of ionic surfactants serve as ideal model systems for “equilibrium polyelectrolytes”. We report systematic light and neutron scattering investigations of the effect of ionic strength, doping level, and total concentration on the static properties of dilute and semidilute micellar solutions. In dilute solutions, we observe a dramatic influence of (intramicellar) electrostatic interactions on the micellar fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 39 publications
4
51
0
Order By: Relevance
“…7 against C D , it seemed that the most linear relationship was obtained compared with other plots; this is consistent with d m being related to the inter-wormlike cylinder distance. We observe exactly the same behaviour as reported for polymer-electrolyte and salt free (or lowionic strength) wormlike micelle solutions (Sommer et al, 2002). Cannavacciuolo et al (2002) carried out a Monte Carlo simulation on systems consisting of many charged wormlike micelles with excluded volume and electrostatic interactions and concluded that the scattering function becomes almost identical with that of uncharged system when the ionic strength is more than 0.1 mol l À1 .…”
Section: Structure Factorssupporting
confidence: 83%
See 1 more Smart Citation
“…7 against C D , it seemed that the most linear relationship was obtained compared with other plots; this is consistent with d m being related to the inter-wormlike cylinder distance. We observe exactly the same behaviour as reported for polymer-electrolyte and salt free (or lowionic strength) wormlike micelle solutions (Sommer et al, 2002). Cannavacciuolo et al (2002) carried out a Monte Carlo simulation on systems consisting of many charged wormlike micelles with excluded volume and electrostatic interactions and concluded that the scattering function becomes almost identical with that of uncharged system when the ionic strength is more than 0.1 mol l À1 .…”
Section: Structure Factorssupporting
confidence: 83%
“…This is because the electrostatic screening due to added salt is large enough to reduce repulsion between charged micelles. Their model was able to accurately reproduce the structural peak of the scattering function for charged micelles (Sommer et al, 2002). The C D dependence of d m in Fig.…”
Section: Structure Factorsmentioning
confidence: 85%
“…The model was originally developed for studying wormlike micelles,28, 29 and most of the applications published in the literature are related to this type of system. The model has also been used in various modified forms for studying electrostatic interactions in charged wormlike micelles, so‐called equilibrium polyelectrolyte chains 29–33…”
Section: Introductionmentioning
confidence: 99%
“…Persistence lengths of the order of 400 Å are typical for neutral wormlike micelles, and have been found repeatedly in the recent literature [27,53,98,100,102,107]. For polyelectrolyte micelles, the total persistence length can be larger than the above characteristic values [108,109]. In conclusion, the persistence length of micellar aggregates is of the order of 400 Å, a value that is between that of synthetic polymers [104] and that of biological molecules, such as DNA, actin and tubulin [110,111].…”
Section: Comparison With Small-angle Neutron Scatteringmentioning
confidence: 80%